2019
DOI: 10.3390/ma12193060
|View full text |Cite
|
Sign up to set email alerts
|

Study on High-Temperature Interaction Mechanism of Nd–Fe–As System

Abstract: In this study, Nd and As are mainly sealed into industrial pure Fe cylinders. The effect of different temperatures on the high-temperature interaction of an Nd–Fe–As ternary system is studied via X-ray diffraction, optical microscopy, and scanning electron microscopy after heat insulation for 30 h at 1173, 1223, and 1273 K. The results show that the common products under high-temperature interaction are NdAs, Fe17Nd2, and Fe. Fe12As5 is present at 1173 K, whereas Fe2As is produced at 1223 and 1273 K. The diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Different atomic ratios of cerium (lanthanum), Fe, and As form the ternary compound RE 12 Fe 57.5 As 41 (RE = La, Ce) and FeAs at 1173 K 21 , 22 , whereas the Re-Fe-As ternary system forms La 10 Fe 50 As 40 23 at 1223 K. In recent years, one of products of RE-Fe-As ternary system named EuFe 2 As 2 24 – 28 has attracted significant attention. Xie 29 and Fu 30 investigated the interaction of Nd–Fe–As system at high temperatures and found that the formation of the ternary compound NdFeAs depends on the formation of NdAs and FeAs 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Different atomic ratios of cerium (lanthanum), Fe, and As form the ternary compound RE 12 Fe 57.5 As 41 (RE = La, Ce) and FeAs at 1173 K 21 , 22 , whereas the Re-Fe-As ternary system forms La 10 Fe 50 As 40 23 at 1223 K. In recent years, one of products of RE-Fe-As ternary system named EuFe 2 As 2 24 – 28 has attracted significant attention. Xie 29 and Fu 30 investigated the interaction of Nd–Fe–As system at high temperatures and found that the formation of the ternary compound NdFeAs depends on the formation of NdAs and FeAs 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As form the ternary compound RE12Fe57.5As41 (RE=La, Ce) and FeAs at 1173 K [13][14] , whereas the Re-Fe-As ternary system forms La10Fe50As40 15 at 1223 K. In recent years, one of products of RE-Fe-As ternary system named EuFe2As2 [16][17][18][19][20] has attracted significant attention. Xie 21 and Fu 22 investigated the interaction of Nd-Fe-As system at high temperatures and found that the formation of the ternary compound NdFeAs depends on the formation of NdAs and FeAs2. Therefore, in this study, a certain quality of Nd and As were sealed in a cylinder block, which was specially processed using industrial pure Fe by melting, infiltration, and diffusion.…”
Section: Introductionmentioning
confidence: 99%